Urban design empowerment through ICT-based platforms in Europe. Issue 2 (2nd April 2020) - Gün, Ahmet; Demir, Yüksel; Pak, Burak
ABSTRACT: The use of ICT-based participation tools in urban design has come into prominence in the last decade. A plethora of technology-enabled participatory tools, techniques, and applications have been developed to facilitate the participation of citizens as well as other stakeholders. This study specifically focuses on ICT-based participation platforms that aim to serve as forums to respond to social and spatial needs. Many studies have reported that the use of these participatory platforms has led to positive outcomes. However, their potentials and limits for facilitating different levels of design empowerment (Senbel and Church, 2011. Design Empowerment. Journal of Planning Education and Research, 31 (4), 423–437.) remain unknown. In this context, the aims of this study are: (1) to determine how these platforms empower and restrict citizens' engagement by analysing a variety of ICT-based participation platforms in Europe, and (2) to determine the factors that can facilitate better participation practices. This research analyses 25 ICT-based participation platforms that go beyond one-sided information exchange. They were chosen out of a database of 106 platforms. These were evaluated according to their objectives, the design action phases in which they are designated to be used, their desired levels of design empowerment and their functionalities. The findings indicate that a majority of these platforms (76%) focused on two particular objectives: problem identification and feedback collection. Only three platforms (12%) enabled users to create their own plans and visions, since empowering citizens to design independently is a challenging task. Many of the platforms aimed at higher levels of design empowerment but failed to provide the required functionalities users need. 40% of the platforms did not have any tools for citizens to track whether their ideas, plans, and projects were implemented or not. In conclusion, we discuss the implications of these findings and identify the key factors for better design practices for ICT-based civic participation platforms.